2014
DOI: 10.1093/molbev/msu057
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Eight Transcriptomes from All Poriferan Classes Reveals Surprising Genetic Complexity in Sponges

Abstract: Sponges (Porifera) are among the earliest evolving metazoans. Their filter-feeding body plan based on choanocyte chambers organized into a complex aquiferous system is so unique among metazoans that it either reflects an early divergence from other animals prior to the evolution of features such as muscles and nerves, or that sponges lost these characters. Analyses of the Amphimedon and Oscarella genomes support this view of uniqueness-many key metazoan genes are absent in these sponges-but whether this is gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
286
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(316 citation statements)
references
References 94 publications
18
286
3
2
Order By: Relevance
“…Isopropylcholesterols, for example, are most common in the order Halichondrida, but can be found sporadically across all major demosponge clades (4). Because A. queenslandica lacks C 30 sterols, we also analyzed the transcriptomes from six additional demosponges (Crella elegans, Ircinia fasciculata, Chondrilla nucula, Pseudospongosorites suberitoides, Spongilla lacustris, and Petrosia ficiformis) (20) as well as genomes from the homoscleromorph sponge Oscarella carmela and calcareous sponge Sycon ciliatum. This larger dataset includes sponges that produce rare C 29 and C 30 sterols (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Isopropylcholesterols, for example, are most common in the order Halichondrida, but can be found sporadically across all major demosponge clades (4). Because A. queenslandica lacks C 30 sterols, we also analyzed the transcriptomes from six additional demosponges (Crella elegans, Ircinia fasciculata, Chondrilla nucula, Pseudospongosorites suberitoides, Spongilla lacustris, and Petrosia ficiformis) (20) as well as genomes from the homoscleromorph sponge Oscarella carmela and calcareous sponge Sycon ciliatum. This larger dataset includes sponges that produce rare C 29 and C 30 sterols (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that one SMT gene is responsible for the first round of methylation of (B) Distribution of sterol synthesis genes across eukaryotes. This phylogeny represents a consensus tree based on previous phylogenetic studies (6,20,35). In some cases, multiple genes have been combined into one category based on shared enzymatic function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now known to be unique to Metazoa [24 -26], a full complement of TGF-b signalling components (TGF-b and BMP ligands, their receptors, and numerous SMAD cofactors) has been found in cnidarians [27 -29], placozoans [15], sponges [30] and, most recently, the ctenophores Mnemiopsis leidyi [31] and Pleurobrachia bachei (table 1). Non-metazoan unikonts lack not only the ligands, receptors and SMAD cofactors [17,[24][25][26], but also most of the inhibitors. This pathway is a clear example of a metazoan innovation [25], and the presence of all elements together in ctenophores suggests that this system was actively transducing extracellular signals into transcriptional responses in the ancestral metazoan.…”
Section: Pathways That Unite Metazoans (A) Transforming Growth Factormentioning
confidence: 99%
“…Alternatively, if sponges are a single clade, we cannot rely upon inferences about the morphology of these nodes to infer the morphological and developmental attributes of the most basal metazoans. Several recent studies suggest that sponges are likely to be monophyletic rather than paraphyletic [8,9]. Earlier studies indicated that resolving the phylogenetic position of ctenophores was complicated by considerable long-branch attraction [10], but more recent studies have attempt to resolve these difficulties and support a basal position for the clade [4,5,11], but have also been criticized [12,13].…”
Section: Rate and Topology Of Early Metazoan Divergencesmentioning
confidence: 99%